What's in It for Them? Advantages of Higher-Status Partners in Exchange Relationships - Castellucci, Fabrizio; Ertug, Gokhan (Academy of Management Journal, 2010)
This article explores the motivations that high-status firms have to enter exchange relationships with lower-status partners. We argue that high-status firms can secure greater effort from lower-status partners and that the amount of effort will be proportional to their status advantage over these partners. We further propose that such effort will translate to increased performance by mediating the negative consequences of affiliations with lower-status partners. This increase in performance constitutes the motivation for high-status firms to enter exchange relationships with lower-status partners. Findings using data on Formula One racing support our argument.